The influence of selected antecedents on athlete endoser credibility, attitude towards an advertisement and purchase intentions - Mahao, Bafokeng Bafokeng (My University, 2017)
Given the pervasive use of celebrity endorsements and the high costs involved in this marketing strategy, it is important for marketers to have knowledge of the right set of procedures to follow in selecting an ambassador to market their products. This study draws from the undertones of Ohanian’s (1990:46) Source attributes theory, comprising elements of the Source credibility theory as well as the Source attractiveness theory. Whereas the former (trustworthiness and expertise) influences consumer attitudes and behaviour through a process called internalisation, the latter (attractiveness) influences receivers of marketing communication messages through a process called identification. The theory is useful when applied during the initial phase of selecting which celebrity to use to endorse products, to avoid costly mistakes of choosing celebrities that do not possess the right set of attributes for persuading consumers. The purpose of this study was to apply the Source attributes theory in understanding the key attributes towards consumers’ evaluations of the credibility of an athlete-celebrity endorser. Moreover, the influence of athlete endorser credibility on consumers’ attitudes and purchase intentions towards the celebrity endorsed advertisement. A quantitative study comprising a non-probability snowball sample of 456 consumers was conducted in 2016, in and around the five major towns of Southern Gauteng province in South Africa. The structured-self administered questionnaire requested participants to indicate their perceptions regarding the attributes of nominated athlete-celebrity, namely, trustworthiness, expertise and attractiveness in endorsing the selected product. In addition, the questionnaire related to consumers’ evaluations of the credibility of the selected athlete-celebrity, consumers’ attitude towards the advertisement where the athlete-celebrity appears and purchase intentions towards the endorsed product. Findings from the study indicated that South African consumers have positive perceptions of the selected athlete-celebrity’s trustworthiness, expertise and attractiveness. In addition, the measurement model was verified using statistical accuracy tests, thereby confirming that the purchase intentions model was a six-factor structure comprising trustworthiness, expertise, attractiveness, endorser credibility, attitude towards the advertisement and purchase intentions. The results of both the confirmatory factor analysis and the structural equation modelling suggest that the three dimensions are valid measures of the overall credibility of the athlete- endorser (R2=0.60). This finding provided support for the scale developed by Ohanian (1990) to be a valid vi measure for selecting celebrity endorsers when applied in South Africa. Moreover, the structural model validated the existence of significant, direct impacts of athlete-endorser credibility on attitude towards the advertisement (path estimate=0.704) and attitude towards the advertisement on purchase intentions (path estimate=0.741). Insights gained from this study will assist both marketing academics and practitioners to understand the perceptions of consumers towards the use of athlete-celebrities in product promotions in the South African market. In this regard, if a determination is made that a celebrity could enhance the marketing campaign, marketers should determine to what extent the celebrity should be used. The correct use of the right celebrity, selected in line with these findings, can help ensure greater consumer persuasion.
M.Tech (Marketing, Faculty of Management Sciences) Vaal University of Technology
Keywords: celebrity endorsement, athlete-endoser, credibility, attitude, purchase intentions; Endorsements in advertising; Marketing management; Advertising research; Dissertations Academic South Africa